THE SPECIAL PRISON REGIME UNDER ARTICLE 41BIS IN ITALY: BETWEEN DETENTION REGIME, ACCESSORY PENALTIES AND PRISONER DEHUMANISATION - DI SALVO, MICHELE (Revista Eletrônica de Direito Processual, 2025)
The proposed article deals in detail with the mechanics of the special prison regime of maximum restriction applied in Italy. This regime is not dissimilar from its counterparts in various prison systems, which may sometimes be more rigid and restrictive in their normative prediction, and at other times more so in their concrete application. If the quality of a democracy is measured by the quality of life in its prisons, to deal with it, especially in regimes of specific fragility of prison life (juvenile prisons, special restriction regimes, psychiatric prisons), is to deal with the civilisation of a country. Psychologists can - and must - do a great deal in this critical and concrete analysis, especially in highlighting the psychologically critical aspects of deprivation regimes. Article 41bis of the Italian Prison Ordinance Law has raised numerous and penetrating constitutionality issues over the years, almost all of them centred on the substantial conflict of the prison legislation with Article 27 paragraph 3 of the Constitution. In addition to a brief examination of the article in question, we will discuss its application, which poses quite a few critical elements in terms of the dehumanisation of the prisoner and the overall system envisaged.